VD_FINDINFO HC / 2014 / 147 vom 14. Februar 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT, MAJORITÉ{ÂGE}, AVANCE DE FRAIS | 176 al. 1 CC, 278 CC, 308 al. 1 let. b CPC (CH)